Analysis of the Effectiveness of Guided Inquiry-Based Physics Learning with the PhET Simulation Guidebook on Global Warming Material: Efforts to Improve Science Process Skills of High School Students - Violita, Selly; Alifah, Rihmah; Okimustava (Jurnal Genesis Indonesia, 2024)
This research aims to develop a guided inquiry-based physics learning guidebook using PhET simulations on global warming material to improve the science process skills of 10th-grade students. The type of research used is development research with a 4D development model. However, this research was carried out only at the development stage, where the product being made would be tested for feasibility first by experts to find out how far the product had been developed. The subjects in this development research were two media experts and two material experts as validators of the guidebook being developed. The media and material expert validation results show that this guidebook falls within the criteria of being quite valid, with a percentage score of 45% from the media expert validation test and 46% from the material expert validation test. This guidebook can be considered a good development based on the development results. It can be used to support physics learning at the high school level, especially regarding global warming.